2015
DOI: 10.3390/v7062762
|View full text |Cite
|
Sign up to set email alerts
|

Important Role of the IL-32 Inflammatory Network in the Host Response against Viral Infection

Abstract: The pro-inflammatory cytokine interleukin (IL)-32 has gained much attention recently because of its important role in the inflammatory network. Since the discovery of IL-32 in 2005, our appreciation for its diverse roles continues to grow. Recent studies have discovered the antiviral effects induced by IL-32 and its associated regulatory mechanisms. The interactions between IL-32 and various cytokines including cyclooxygenase 2 (COX-2), inducible nitric oxide synthase (iNOS), interferon (IFN)-λ1, interleukin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 82 publications
1
29
0
Order By: Relevance
“…These data are also in agreement with other group's findings, showing that COX-2/PGE 2 production inhibits viral replication via the upregulation of antiviral cytokines (i.e. IL-32, IL-27, IFN-λ1) [30][31]49] in A549 cells. In contrast to our observation, it has been reported that inhibition of COX-2 and PGE 2 enhanced antiviral activity against virus infection in various kinds of cells [50][51][52].…”
Section: Discussionsupporting
confidence: 93%
“…These data are also in agreement with other group's findings, showing that COX-2/PGE 2 production inhibits viral replication via the upregulation of antiviral cytokines (i.e. IL-32, IL-27, IFN-λ1) [30][31]49] in A549 cells. In contrast to our observation, it has been reported that inhibition of COX-2 and PGE 2 enhanced antiviral activity against virus infection in various kinds of cells [50][51][52].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, cytokines related to cytokine release syndrome (such as IL-1A/B, IL-6, IL-10, IL-18, and TNFA), showed increased positive association to the severity of the disease in the blood from COVID-19 patients [49]. Another proinflammatory cytokine specifically upregulated in SARS-CoV-2 infected cells was IL-32, which together with CSF2, promotes the release of TNF and IL-6 in a continuous positive loop and therefore contribute to this cytokine storm [90]. Interestingly, IL-6, IL-7 and IL-18 were found to be upregulated in two of the four data sets of SARS-CoV-2 infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…IL-32 is cytokine known to its important biological functions. Due to its proinflammatory function, IL-32 induces production of different chemokines and pro-inflammatory cytokines, including IL-1β, TNF-α, IL-6, IL-8, and macrophage inflammatory protein-2 (MIP-2) and activation of the p38 mitogen-activated protein kinase (MAPK), nuclear factor κB (NF-κB), and activator protein-1 (AP-1) signaling pathways (27). IL-32 plays role in genesis and progression of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%